Find solutions to your problems with the help of IDNLearn.com's expert community. Our experts provide timely, comprehensive responses to ensure you have the information you need.
Sagot :
To solve the equation [tex]\( n^3 - 9n^2 - n + 9 = 0 \)[/tex] using factoring by grouping, follow these steps:
1. Group the terms:
Separate the polynomial into two groups:
[tex]\[ (n^3 - 9n^2) + (-n + 9) \][/tex]
2. Factor out the greatest common factor (GCF) from each group:
From the first group [tex]\( n^3 - 9n^2 \)[/tex], the GCF is [tex]\( n^2 \)[/tex]. Factor it out:
[tex]\[ n^2(n - 9) \][/tex]
From the second group [tex]\( -n + 9 \)[/tex], the GCF is [tex]\(-1\)[/tex]. Factor it out:
[tex]\[ -1(n - 9) \][/tex]
Putting this together, we have:
[tex]\[ n^2(n - 9) - 1(n - 9) = 0 \][/tex]
3. Factor by grouping:
Notice that [tex]\( (n - 9) \)[/tex] is a common factor in both terms:
[tex]\[ (n^2 - 1)(n - 9) = 0 \][/tex]
4. Factor the quadratic expression:
The expression [tex]\( n^2 - 1 \)[/tex] is a difference of squares and can be factored further:
[tex]\[ (n + 1)(n - 1)(n - 9) = 0 \][/tex]
5. Solve for [tex]\( n \)[/tex]:
Set each factor to zero and solve for [tex]\( n \)[/tex]:
[tex]\[ n + 1 = 0 \quad \Rightarrow \quad n = -1 \][/tex]
[tex]\[ n - 1 = 0 \quad \Rightarrow \quad n = 1 \][/tex]
[tex]\[ n - 9 = 0 \quad \Rightarrow \quad n = 9 \][/tex]
Thus, the solutions to the equation [tex]\( n^3 - 9n^2 - n + 9 = 0 \)[/tex] are:
[tex]\[ \boxed{-1, 1, 9} \][/tex]
1. Group the terms:
Separate the polynomial into two groups:
[tex]\[ (n^3 - 9n^2) + (-n + 9) \][/tex]
2. Factor out the greatest common factor (GCF) from each group:
From the first group [tex]\( n^3 - 9n^2 \)[/tex], the GCF is [tex]\( n^2 \)[/tex]. Factor it out:
[tex]\[ n^2(n - 9) \][/tex]
From the second group [tex]\( -n + 9 \)[/tex], the GCF is [tex]\(-1\)[/tex]. Factor it out:
[tex]\[ -1(n - 9) \][/tex]
Putting this together, we have:
[tex]\[ n^2(n - 9) - 1(n - 9) = 0 \][/tex]
3. Factor by grouping:
Notice that [tex]\( (n - 9) \)[/tex] is a common factor in both terms:
[tex]\[ (n^2 - 1)(n - 9) = 0 \][/tex]
4. Factor the quadratic expression:
The expression [tex]\( n^2 - 1 \)[/tex] is a difference of squares and can be factored further:
[tex]\[ (n + 1)(n - 1)(n - 9) = 0 \][/tex]
5. Solve for [tex]\( n \)[/tex]:
Set each factor to zero and solve for [tex]\( n \)[/tex]:
[tex]\[ n + 1 = 0 \quad \Rightarrow \quad n = -1 \][/tex]
[tex]\[ n - 1 = 0 \quad \Rightarrow \quad n = 1 \][/tex]
[tex]\[ n - 9 = 0 \quad \Rightarrow \quad n = 9 \][/tex]
Thus, the solutions to the equation [tex]\( n^3 - 9n^2 - n + 9 = 0 \)[/tex] are:
[tex]\[ \boxed{-1, 1, 9} \][/tex]
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.